Introduction of Biofuels as a Way of Solving Ecological Problems - Burkhardt, Thomas; Stepanova, Diana; Ratkin, Leonid; Ismailov, Ismail; Lavrushin, Oleg; Sokolinskaya, Natalia; Danish, Mir Sayed Shah; Senjyu, Tomonobu; Yuksel, Serhat; Dincer, Hasan (International Journal of Energy Economics and Policy, 2021)
Since environmental issues have become a priority for everyone on the planet, and the fact that growing demand for fossil fuels will soon lead to a reduction in world reserves, except for climate change due to their use and greenhouse gas emissions. The aim of this work was to assess the potential for the introduction of biofuels and find the optimal conditions for the enzymatic hydrolysis of Japonica Rice husk. In addition, evaluate the positive and negative consequences because of the use and implementation of this technology. The methodology used variables: substrate FPU, pH, time, temperature and concentration surfactants using the screening construct obtained statistically, all variables are significant. Then an optimization plan was applied for the variables: pH, FPU and time, dropping those with a lower level of significance. Finally, the best conditions found in previous projects were (pH 5.0, 13 h, and 30 FPU / g of substrate); later, these conditions were applied in experiments to assess the effect of an increase in hydrolyzed cellulose. They use 6%; 8% and 10% of pulp is available with a recycling yield of 74%, 42% and 16%. The community has its own interests in the use of biofuels; therefore, this study provides an opportunity for biofuel producers to reduce environmental, economic, and social costs. Keywords: biofuel; environment; alternative energy; bioethanol. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.10686